EFFECT OF WORKLOAD AND WORK ENVIRONMENT ON WORK MOTIVATION AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE AT PT CIPTAJAYA SEJAHTERA ABADI - Happy Nur Fitri Handayani (Dinasti International Journal of Education Management And Social Science, 2022)
This research aims to find out and analyze related to the influence of workload and work environment with work motivation as a mediation variable in PT Ciptajaya Sejahtera Abadi. This study method uses quantitative research with causal methods. The population for this study was an employee of PT Ciptajaya Sejahtera Abadi as many as 220 people and for the study sample using the slovin formula to 142 respondents. Data collection uses primary data and secondary data. Technical data analysis uses path analysis methods (Path Models) with the help of SmartPLS version 3.2.9. The results showed that work sacrifices have a negative and significant effect on employee performance. Workload has a negative and significant effect on work motivation.The work environment has a positive and significant effect on employee performance.The work environment has a positive and significant effect on work motivation. Work motivation has a negative and significant effect on employee performance. Workload and work environment have a positive and significant effect on employee performance. Workload, work environment and work motivation have a positive and significant effect on employee performance. Work motivation has no mediating effect on workload on employee performance. Work motivation has no mediating effect on the work environment on employee performance.